2008
DOI: 10.1002/jmri.21413
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using real‐time MRI to measure joint kinematics in 1.5T and open‐bore 0.5T systems

Abstract: Purpose: To test the feasibility and accuracy of measuring joint motion with real-time MRI in a 1.5T scanner and in a 0.5T open-bore scanner and to assess the dependence of measurement accuracy on movement speed. Materials and Methods:We developed an MRI-compatible motion phantom to evaluate the accuracy of tracking bone positions with real-time MRI for varying movement speeds. The measurement error was determined by comparing phantom positions estimated from real-time MRI to those measured using optical motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 56 publications
0
48
0
Order By: Relevance
“…11 Techniques such as real-time ultrafast MRI using a combination of a fast low-angle shot (FLASH) or true fast imaging with steady-state precession (FISP) sequence with radial data sampling and view sharing of successive acquisitions allow for high-speed and motion-robust examinations. 12-17 This allows for a temporal resolution of up to 50 milliseconds per frame and low-latency online display of the images without the need for offline processing on external hardware.…”
mentioning
confidence: 99%
“…11 Techniques such as real-time ultrafast MRI using a combination of a fast low-angle shot (FLASH) or true fast imaging with steady-state precession (FISP) sequence with radial data sampling and view sharing of successive acquisitions allow for high-speed and motion-robust examinations. 12-17 This allows for a temporal resolution of up to 50 milliseconds per frame and low-latency online display of the images without the need for offline processing on external hardware.…”
mentioning
confidence: 99%
“…In a preclinical study, adequate tracking of the area of interest has been demonstrated up to speeds of 1.5 cm per second using a phantom [9]. In another phantom study, measurement accuracies within 2 mm were possible up to velocities of 38 mm per second [16].…”
Section: Discussionmentioning
confidence: 98%
“…With respect to dynamic MRI, our method is less expensive and more accurate [4]. Compared to actual clinical procedures, that are based on a previous static CT or MRI scan and a manual fitting of the shape, this method is less expensive (as CT and MRI can be avoided) and more accurate due to the automatic fitting.…”
Section: Discussionmentioning
confidence: 99%
“…However, it can only be used with relatively slow movements, and the accuracy obtained increases from 1mm to more than 3mm depending from the velocity of the movement. In addition, MRI scans are highly expensive [4]. Traditional CT and MRI provide an accurate evaluation of the morphology of the knee, but are limited to static positioning of the patient.…”
Section: Fig8 : "Exted" -> "Extend"mentioning
confidence: 99%